Influence of high loss liquid on the bandwidth of a circular two-layer waveguide at microwaves. Issue 14 (22nd September 2018) - Kuznetsova, Kateryna S.; Eremenko, Zoya E.
ABSTRACT: The electromagnetic waves propagation in a circular two-layer metal waveguide with a central low-loss dielectric rod surrounded by high loss liquid is studied in the microwave range. The dependence of the complex wave propagation coefficient on frequency and liquid layer thickness is obtained. The presence of high loss liquid surrounding the dielectric rod allows expanding the range of operating wavelengths of the standard waveguide from the millimeter to centimeter range, because the wave attenuation coefficient remains relatively small. We find that owing to a high loss liquid, such a waveguide does not have fixed values of cut-off frequencies. An extra low value of the wave attenuation coefficient is found in the centimeter wavelength range at certain liquid layer thicknesses. The proposed structure can be applied as a measuring cell for the determination of the complex permittivity of high loss liquids in small volumes and in a wide range of wavelengths.